ANTHROPOCENTRIC LINGUISTICS AND AI INTEGRATION: A MODERN PERSPECTIVE (Educator Insights: Journal of Teaching Theory and Practice, 2025)
This article explores the intersection of anthropocentric linguistics and modern artificial intelligence (AI) technologies, highlighting how human-centered linguistic theory can guide the responsible development of intelligent systems. The expanded analysis discusses the origins of anthropocentrism in linguistics, its methodological evolution, and its implications for AI modeling. The article also reviews cross-linguistic relevance, with a particular emphasis on Uzbek linguistics, including ethnolinguistic, pragmatic, and cognitive studies that can enrich AI systems. The study concludes with recommendations for applying anthropocentric principles in AI-driven education, translation, and digital communication.